PELATIHAN PENGUATAN LITERASI SAINS UNTUK ANAK SEKOLAH DASAR DESA MANYARSIDORUKUN GRESIK - Siti Amaliati; Ismawati Ismawati (Mafaza : Jurnal Pengabdian Masyarakat, 2023)
This research advocates for an instructional approach that involves optimizing children's sensory engagement through the direct experiential exploration to enhance effective learning. By providing opportunities for hands-on learning experiences, this method aims to assist children in developing analytical skills and critical thinking abilities. Critical thinking skills are crucial for children to confront future challenges. Cultivating critical thinking by enhancing scientific literacy in children involves helping them grasp scientific concepts, observe natural phenomena, conduct experiments, and understand scientific processes. This enables children to develop their critical thinking abilities. However, many schools face challenges in facilitating experimental learning due to various factors and reasons. Therefore, this Community Engagement Initiative focuses on empowering elementary school-aged children by strengthening their scientific literacy through the introduction of "temperature and heat" concepts. This material can help children deepen their understanding of the world around them in a more profound yet simple manner. This Community Engagement Initiative employs a training method with the following stages: 1) discussions with schools to identify students' needs, 2) problem identification, 3) activity planning, 4) implementation of activities, 5) activity evaluation, and 6) activity reporting. The partners in this community engagement are the "literacy house" community in the village of Manyarsidorukun, Gresik, and lecturers from the Daruttaqwa Islamic Institute, Gresik. The outcomes of this initiative include 1) Children feel delighted with this PkM activity as participants can practice directly 2) Develop communication skills by retelling their learning experiences.